(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the language and artistry of the novel “Qissai Sayqaliy” by Sobir Sayqaliy, in which, along with the language that provides the charm of this work, the fertile use of artistic means of painting, revealing the character and spirit of the heroes of the work, was fundamentally analyzed during the citation of the work.